2019
DOI: 10.1002/jcp.28168
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic roles of TRPM ion channels in cancer

Abstract: Transient receptor potential (TRP) proteins are a diverse family of ion channels present in multiple types of tissues. They function as gatekeepers for responses to sensory stimuli including temperature, vision, taste, and pain through their activities in conducting ion fluxes. The TRPM (melastatin) subfamily consists of eight members (i.e., TRPM1–8), which collectively regulate fluxes of various types of cations such as K+, Na+, Ca2+, and Mg2+. Growing evidence in the past two decades indicates that TRPM ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 178 publications
(297 reference statements)
0
20
0
Order By: Relevance
“…The results suggested that certain members of the TRPM family may be potential biomarkers and targets for new breast cancer therapies. Associations between TRPM proteins and breast cancer continue to be identified as a result of rapid advances in molecular biology and genetics research ( 9 ). In addition, TRPM6 somatic mutations have also been observed in an independent cohort of breast cancer samples ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that certain members of the TRPM family may be potential biomarkers and targets for new breast cancer therapies. Associations between TRPM proteins and breast cancer continue to be identified as a result of rapid advances in molecular biology and genetics research ( 9 ). In addition, TRPM6 somatic mutations have also been observed in an independent cohort of breast cancer samples ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7 has been considered to regulate the migration and invasion of metastatic breast cancer cells ( 7 ). Taken together, the TRPM protein family may be attractive targets for anticancer therapies or prognostic biomarkers in certain types of human cancer ( 8 , 9 ). However, to the best of our knowledge, a systematic study on the transcriptional expression and prognostic value of the TRPM protein family members in human tumors has not been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…As the subclass of the TRP channels, TRPMs have varying permeability to Ca 2+ and Mg 2+ in various types of cancer (5,26,27). Therefore, TRPM protein family members may serve attractive targets for anticancer therapeutic strategies or prognostic biomarkers to cure specific types of cancers (26,28). It is common knowledge that TRPM8 is involved in the initiation and progression of tumors (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings undoubtledly require scrutinization, they suggested that TRPM8 may be involved in the transformation of normal cells to tumorigenic cells, which culminates in biological changes, such as tumor proliferation, apoptosis, gene transcription and angiogenesis (31). Morever, few studies have been performed where the gene expression data is correlated with the survival of patients (8,9,11,28). Combined, TRPM8 may serve as an appropriate GBM biomarker, and this biomarker is urgently required for the early diagnosis and validation of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…They function as gatekeepers by mediating ion fluxes in response to various sensory stimulus including temperature, vision, taste, and pain [1]. In mammals, the TRP superfamily includes 28 members, which can be subdivided into 6 subfamilies: TRPA (ankyrin), TRPC (canonical), TRPM (melastatin), TRPML (mucolipin), TRPP (polycystin), and TRPV, but humans only express 27 TRP channel members [2,3]. There are eight members in the TRPM subfamily (TRPM1-8), and each member consists of six transmembrane domains with a pore-forming loop, and the N-and C-termini directed to the cytoplasm.…”
mentioning
confidence: 99%